Deep brain stimulation-guided optogenetic rescue of parkinsonian symptoms - Sébastien Valverde (Nature Portfolio, 2020)
Deep brain stimulation (DBS) is a symptomatic treatment of Parkinson’s disease (PD) that benefits only a minority of patients. Here, the authors show that activation of cortical somatostatin interneurons alleviates motor symptoms in a mouse model of PD and may constitute a less invasive alternative than DBS.